Advective transport caused by intraseasonal Rossby waves : A key player of the high chlorophyll variability off the Peru upwelling region - Bonhomme, Céline; Aumont, Olivier; Echevin, Vincent. (Journal of Geophysical Research Oceans, 2007)
The upwelling region off Peru between 5 degrees S and 12 degrees S is characterized by high offshore intraseasonal variability in sea-surface productivity due to westward propagating chlorophyll anomalies, whose magnitude can reach half the variance of total chlorophyll variations. Spectral analyses of SSH, SST and chlorophyll satellite data show that these events are generated by intraseasonal Rossby waves. The almost constant phase shift between chlorophyll and altimetric signals suggests a physical mechanism dominated by horizontal advection, which is confirmed by the use of a simple conceptual model. Furthermore, an increase from the north to the south in the detected Rossby wave periods, correlated with a decrease in the wavelengths and phase velocities of the wave, suggests the presence of a second baroclinic mode north of 8 degrees S and of a first baroclinic mode south of this latitude. The latitude of this transition is consistent with the theory of critical latitudes, which specifies that at a given latitude, only Rossby wave with periods below a threshold period, depending on the baroclinic structure of the wave, can propagate offshore. According to this theory, second baroclinic mode Rossby waves with periods greater than 130 days are supposed to propagate off the South American coast north of 8 degrees S, the corresponding critical latitude.